Penerapan Metode SMART dalam Sistem Pendukung Keputusan Penentuan Kelayakan Pemberian Kredit pada Koperasi Cipta Usaha Mandiri Berbasis Web - Yustin Kurniawan Harefa; Alvino Octaviano (CV. Multi Kreasi Media, 2026)
This research aims to design and implement a web-based Decision Support System (DSS) capable of assisting in determining credit eligibility more quickly, accurately, and objectively by applying the SMART (Simple Multi-Attribute Rating Technique) method. The SMART method was chosen because it has a simple yet effective calculation process for processing various assessment criteria. The criteria used in this study include income, credit history, collateral, number of dependents, and length of business. The research method used was quantitative, with data collection techniques including observation, interviews, and literature review. The system was developed using the Waterfall method, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. The results show that the system is capable of automatically calculating and ranking prospective loan recipients based on the weight and value of each criterion. Furthermore, Black Box Testing results indicate that all system functions operate according to established requirements. Therefore, the application of the SMART method in a web-based decision support system can help the Cipta Usaha Mandiri Cooperative improve the effectiveness, efficiency, transparency, and accuracy of its credit decision-making process, thereby minimizing risk assessment errors and the risk of bad debts